Appropriateness of Anti-MRSA Therapy in Hospitalized Patients With Suspected Community-Onset Infections. (October 2020) - Springer, Sydney; Burk, Muriel; Echevarria, Kelly; Jones, Makoto; Goetz, Matthew
Abstract : Background: Inappropriate use of MRSA-spectrum antibiotics is an important antimicrobial stewardship target. Contributors to inappropriate use include empiric treatment of patients who are determined to not be infected or who are infected but lack MRSA risk factors, and by excessive treatment duration when suspected MRSA infection is disproven. To characterize opportunities for improvement, we conducted a medical use evaluation (MUE) in 27 VA medical centers. The primary objectives were to assess the following proportions: (1) courses of unjustified empiric vancomycin therapy (patients in whom all antibacterials were halted within 2 days or without a principal or secondary discharge infection diagnosis); (2) courses of unjustified continuation of anti-MRSA therapy beyond day 4 (no MRSA risk factors or proven MRSA infection); and (3) excess anti-MRSA days of therapy (DOT), that is, DOT in unjustified empiric courses plus DOT after day 4 in unjustified continued courses. Methods: Clinical pharmacists performed retrospective, structured, manual record reviews of patients started on intravenous vancomycin on day 1 or 2 of hospitalization from June 2017 to May 2018. Exclusion criteria included surgical prophylaxis, recent MRSA infection, β-lactam allergy, renal insufficiency, severe immunosuppression, or infection that warranted anti-MRSA therapy other than vancomycin. Results: Of 2, 493 evaluated patients, 1, 320 met the inclusion criteria. Among them, 44% of courses were initiated in the emergency department, 37% of patients had ≥1 risk factor for healthcare-associated infections, and 50% of patients had ≥2 SIRS criteria or required vasopressor support. The most common admission diagnoses were skin and soft-tissue infection (SSTI, 40%; 68% nonpurulent) and pneumonia (27%; 46% without healthcare risk factors). Clinical cultures recovered MRSA from 8% of patients. Empiric therapy was not justified in 342 patients (26%; 57% were clinically stable). Continued therapy was unjustified in 46% of the 320 patients who received >4 days of anti-MRSA therapy. Of all days of anti-MRSA therapy, 23% were unjustified; 65% of these were due to unjustified empiric therapy. Site-specific variations in unjustified empiric therapy better correlated with the proportion of unjustified DOT than did unjustified continuation of therapy (Pearson correlation coefficients [PCC], 0.75 and 0.54, respectively) (Fig. 1). Facility-specific proportions of unjustified DOT modestly correlated with anti-MRSA DOT (PCC, 0.45; n = 27) (Fig. 2) but not the anti-MRSA standardized antimicrobial administration ratio (PCC, 0.15; n = 21). Conclusions: In this multicenter MUE, 26% of all days of anti-MRSA therapy lacked justification; this rate correlated with total facility-specific anti-MRSA DOT. Unnecessary empiric therapy, largely in the ED and for nonpurulent SSTIs and pneumonia without risk factors, was the principal contributor to unjustified DOT. Funding: None Disclosures: None